The Influence of Adding Api-Api Mangrove Leaf Extract as an Immunostimulant on Vaname Shrimp Against Vibriosis Disease Caused by Vibrio parahaemolyticus Bacteria - Anjani Arum Mahenda; Misbakhul Munir; Dian Sari Maisaroh (Pelopor Publikasi Akademika, 2023)
Vanname shrimp cultivation is one of the most developed aquacultures in Indonesia and makes it one of the commodities with the highest foreign exchange inputs for the Indonesian state from the fisheries sector. Disease attack is one of the main causes of failure in vaname shrimp culture, especially disease attacks caused by Vibrio parahaemolyticus bacteria. Avicennia alba mangrove leaf extract is known to have active compounds that can act as antibacterial. This research was conducted by mixing Avicennia alba mangrove leaf extract with doses of 150 ppm (VA), 250 ppm (VB) and 350 ppm (VC) into commercial feed by re-pelletting. Positive control (KV+) treatment used commercial vitamins added to the feed. The vaname shrimp used was 60 days old with an average initial weight of 8.9 grams. The aquariums used were 15 pieces with a size of 60 x 30 x 40 cm and a volume of 54 liters of water. The white shrimp challenge test with Vibrio parahaemolyticus bacteria with a concentration of 106 Cfu/ml as much as 0.2 ml. The clinical symptoms of white vaname shrimp include pale white hepatopancreas, blackened tail, grippy swimming legs, necrosis in some parts of the body, necrosis of the tail, blackened and necrotic rectum, broken intestines that are partially brown and starting to turn white, empty intestines, presence of white feces. appears in the aquarium, decreased appetite, as well as not actively swimming. The results showed that Avicennia alba leaf extract had an effect on absolute weight growth (W), growth rate (GR), specific growth rate (SGR), survival rate (SR), total haemocyte count (THC) and phagocytic activity of white shrimp. The dose of 350 ppm VC treatment was the most influential dose as an immunostimulant in this study.